Validity and reliability of knowledge, attitude and practice questionnaires on the transmission of influenza a (h1n1) epidemic - Bassir, Abd Hamid (2010)
Influenza A (HlNl) is a new disease that inf~cts human. The disease leads to the increasing incidence in many countries in the world and cause the occurrence of several large outbreaks in year 2009. In Malaysia, the total number of death was 79. The Minister of Health Malaysia also announced that there were possibilities that the virus could generate a deadlier second wave and may lead to a national health emergency. The objective of this study was to validate the knowledge, attitude and practice of HlNl questionnaires (KAPHINIQ) and evaluating the level of .knowledge, attitude and practice of Malaysian people in response of current situation of pandemic influenza A (HINt) infection. The cross sectional study was carried out at Pasir Mas Health Clinic. A standardized selfadministered questionnaires regarding knowledge, attitude and practice of influenza A (HINt) were used to interview 171 respondents who attended the Pasir Mas Health Clinic. Reliability was assessed by Cronbach's alpha. Construct validity was assessed using exploratory factor analysis. Both validity and reliability were tested separately for each domain of knowledge, attitude and practice. The result of reliability of three domains showed satisfactory reliability with Cronbach's alpha of knowledge domain was between 0.560 and 0.633, Cronbach's alpha of attitude domains was between 0.716 and 0.844 and Cronbach's alpha of practice domain was between 0.794 and 0.824. The questionnaires also showed satisfactory validity with factor loading of items in the knowledge domain range from 0.435 to 0.788, factor loading of items in the attitude domain range from 0.634 to 0.949 and factor loading of items in the attitude domain range from 0.401 to 0.910. There were five items of knowledge domain were deleted because the items had poor relationship to the knowledge domain. As the conclusion the KAPHlNIQ is valid and reliable to assess the Malaysian people toward their knowledge, attitude and practice towards influenza A (H1N1) infection. It is recommended to use this KAPH1 N1 Q for other Malaysian people such as school children, people in rural area and people in other institutions such as universities.